Identification of Cyanobacteria in a Eutrophic Coastal Lagoon on the Southern Baltic Coast - Albrecht, Martin; Pröschold, Thomas; Schumann, Rhena (Frontiers in Microbiology, 2017)
Cyanobacteria are found worldwide in various habitats. Members of the picocyanobacteria genera Synechococcus and Prochlorococcus dominate in oligotrophic ocean waters. Other picocyanobacteria dominate in eutrophic fresh or brackish waters. Usually, these are morphologically determined as species of the order Chroococcales / clade B2. The phytoplankton of a shallow, eutrophic brackish lagoon was investigated. Phytoplankton was dominated by Aphanothece-like morphospecies year-round for more than 20 years, along a trophy and salinity gradient. A biphasic approach using a culture-independent and a culture-dependent analysis was applied to identify the dominant species genetically. The 16S rRNA gene phylogeny of clone sequences and isolates indicated the dominance of Cyanobium species (order Synechococcales sensu Komárek / clade C1 sensu Shih). This difference between morphologically and genetically based species identifications has consequences for applying the Reynolds functional-groups system, and for validity long-term monitoring data. The literature shows the same pattern as our results: morphologically, Aphanothece-like species are abundant in eutrophic shallow lagoons, and genetically, Cyanobium is found in similar habitats. This discrepancy is found worldwide in the literature on fresh- and brackish-water habitats. Thus, most Aphanothece-like morphospecies may be, genetically, members of Cyanobium.